States should take a prudential approach to the implementation of GLoBE rules to avoid ISDS - Fernando Bedoya; Belén Lassala (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
The implementation of the GloBE rules deriving from the OECD Inclusive Framework on Base Erosion and Profit Shifting can potentially impact investor's rights under international investment agreements, through the withdrawal of tax incentives. This Perspective identifies ways to limit States' exposure to investor-state dispute settlement.
Keywords: 330